Kredibilitas Hadis dalam COVID-19: Studi atas Bażl al-Mā’ūn fi Fadhli al-Thāun karya Ibnu Hajar al-Asqalany - Saifuddin Zuhri Qudsy; Ahmad Sholahuddin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
This paper discusses the work of Ibn Hajar al-Asqalany, which has been discussed by Islamic scholars around the world. His description of the pandemic was quite comprehensive, including the encyclopedia data of the plague that occurred during the Shahabah, Umayyad and Abbasid dynasties. By departing from the questions: first, how does Islamic literature talk about a pandemic; secondly, what are the factors that cause pandemic emerged in Islamic history literature? Third how is the credibility of Bażl al-Mā’ūn and others in dealing with pandemics such as COVID-19? This paper shows that Bażl al-Mā'ūn is an important reference in discussing pandemics in the Islamic world.Besides, there are indeed other books that appeared before al-Asqalany's work which also shows that basically the Islamic religion has strong credibility for talking about a pandemic in many perspectives, not only from a religious point of view, but from an empirical and scientific point of view.